Examination of Postmortem β-Hydroxybutyrate Increase in Forensic Autopsy Cases - Hiroki Kondou; Risa Bandou; Hiroaki Ichioka; Ryota Matsunari; Masataka Kawamoto; Nozomi Idota; Deng Ting; Satoko Kimura; Hiroshi Ikegaya (Applied Sciences, 2022)
Ketoacidosis is one of the common diseases that sometimes result in death. In forensic autopsy cases, the measuring of ketone bodies, especially β-hydroxybutyrate (BHB), is useful in diagnosing postmortem ketoacidosis as a cause of death. However, increased BHB values are not always indicative of ketoacidosis. Other causes of death, such as hypothermia, are known to increase BHB values. In addition, sometimes, we experience cases of increased BHB values that are unlikely to be associated with the pathophysiology or the cause of death resulting in an increase in BHB values. In this study, autopsies were performed to determine the relationship between blood BHB values and the postmortem interval (PMI). The patients were divided into four groups: PMI ≤ 24 h, PMI ≤ 48 h, PMI ≤ 72 h, and PMI > 72 h. The BHB values for each group were then compared. Based on the analysis, patients with a PMI ≤ 72 h and those with a PMI > 72 h had significantly higher BHB values than patients with a PMI ≤ 24 h. In conclusion, there remains a possibility that the BHB values increase after death. Forensic pathologists should consider PMI when diagnosing ketoacidosis as the cause of death.